Association between albumin infusion and septic patients with coronary heart disease: A retrospective study based on medical information mart for intensive care III database - Ye, Zhiwen; Gao, Ming; Ge, Chenglong; Lin, Wenrui; Zhang, Lina; Zou, Yu; Peng, Qianyi (Frontiers in Cardiovascular Medicine, 2022)
Coronary heart disease (CHD) was a common comorbidity in Intensive Care Unit (ICU) patients especially in the elderly. This particular population may get a worse condition under the attack of sepsis and make an overwhelming challenge for clinical practice. Previous researches suggested patients with CHD had an increased risk for cardiovascular events and low albumin concentration worsened prognosis of patients with stable CHD. Although hypoalbuminemia in septic patients is common due to nutrition disorder, excess consumption and leakage. Simultaneously albumin is a kind of fluid often used for resuscitation in septic patients. However, albumin infusion in septic patients with CHD was rarely studied. The effect and safety on septic patients with CHD regarding albumin infusion remained unclear. Therefore, we collected the medical information from Mimic-III (Mimic-III) and compared the all-cause mortality and cardiovascular mortality at 28-day or 90-day between the albumin group and the non-albumin group on septic patients with CHD. A total of 2027 patents with sepsis and CHD were included in our research, with 405 in the albumin and 1622 in the non-albumin group respectively. After propensity-score matching (PSM), 350 pairs were enrolled in our study. An improved survival benefits was found in the albumin group at the 28-day all-cause mortality compared to the non-albumin group (HR 0.57; 95% CI 0.40-0.81; P=0.001). However, no difference was defected at the 90-day survival benefits (HR 0.85, 95% CI 0.63-1.11, P=0.215). Albumin infusion did not reverse the cardiovascular mortality neither at 28-day nor 90-day (cardiovascular mortality: 28-days, HR 0.56, 95% CI 0.25-1.25, P=0.156; 90-days, HR 0.71, 95% CI 0.36-1.40, P=0.317).